2021
DOI: 10.3389/fmicb.2020.598507
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Biochemical and Genomic Characterization of Glyphosate Tolerant Bacteria to Perform Microbe-Assisted Phytoremediation

Abstract: The large-scale use of the herbicide glyphosate leads to growing ecotoxicological and human health concerns. Microbe-assisted phytoremediation arises as a good option to remove, contain, or degrade glyphosate from soils and waterbodies, and thus avoid further spreading to non-target areas. To achieve this, availability of plant-colonizing, glyphosate-tolerant and -degrading strains is required and at the same time, it must be linked to plant-microorganism interaction studies focusing on a substantive ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 105 publications
0
5
0
1
Order By: Relevance
“…Ochrobactrum haematophilum P6BS-III and Rhizobium sp. P44RR-XXI were inoculated into soil microcosms but did not produce significant differences compared with the noninoculated soil . Therefore, this is an important issue for future research into how specific microbial degraders act at high potency in glyphosate remediation and how they synergistically act with indigenous microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Ochrobactrum haematophilum P6BS-III and Rhizobium sp. P44RR-XXI were inoculated into soil microcosms but did not produce significant differences compared with the noninoculated soil . Therefore, this is an important issue for future research into how specific microbial degraders act at high potency in glyphosate remediation and how they synergistically act with indigenous microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Unclassified genera accounting for 10.11 % and 5.90% in anodic biofilms and non-MESs cultures respectively, may also have important roles in glyphosate degradation. Other identified genera that have currently been isolated as glyphosate-degraders include Achromobacter, Agrobacterium, Comamonas, Achromobacter, Ochrobactrum, Geobacillus and Rhizobium (Massot et al, 2021; Zhan et al, 2018). In the present study, none of these genera were found in the initial inoculum nor after microbial enrichment.…”
Section: Resultsmentioning
confidence: 99%
“…En contraste, se registró que Rhizobium sp. P44RR-XXIV metaboliza el 50% de glifosato en nueve días (Massot et al, 2021), y especies o genotipos de Bradyrhizobium spp. podrían ser un potencial degradador de glifosato en el suelo, ya que el gen glicina oxidasa (thiO) involucrado en la oxidación del glifosato a AMPA tuvo una relación positiva entre la abundancia del gen thiO y el glifosato degradado en AMPA (Hernández et al, 2021).…”
Section: Factor Agroquímico: Herbicidas Glifosatadosunclassified